Indigenous Youth Peer-Led Health Promotion in Canada, New Zealand, Australia, and the United States: A Systematic Review of the Approaches, Study Designs, and Effectiveness - Vujcich, Daniel; Thomas, Jessica; Crawford, Katy; Ward, James (Frontiers in Public Health, 2018)
Background: Youth peer-led interventions have become a popular way of sharing health information with young people and appear well suited to Indigenous community contexts. However, no systematic reviews focussing on Indigenous youth have been published. We conducted a systematic review to understand the range and characteristics of Indigenous youth-led health promotion projects implemented and their effectiveness. Methods: A systematic search of Medline, Embase and ProQuest Social Sciences databases was conducted, supplemented by grey literature searches. Included studies focussed on interventions where young Indigenous people delivered health information to age-matched peers. Results: Twenty four studies were identified for inclusion, based on 20 interventions (nine Australian, four Canadian and seven from the United States of America). Only one intervention was evaluated using a randomised controlled study design. The majority of evaluations took the form of pre-post studies. Methodological limitations were identified in a majority of studies. Study outcomes included improved knowledge, attitude and behaviours. Conclusion: Currently there is limited high quality evidence for the effectiveness of peer-led health interventions with Indigenous young people, and the literature is dominated by Australian-based sexual health interventions. More systematic research investigating the effectiveness of peer-led inventions is required, specifically with Indigenous populations. In order to improve health outcomes for Indigenous youth, greater knowledge of the mechanisms and context under which peer delivered health promotion is effective in comparison to other methods of health promotion is needed.